Systematic review and classification of: Coping Cat - Haugland, Bente Storm Mowatt; Bjåstad, Jon Fauskanger (Ungsinn. Journal of Effective Interventions for Children and Adolescents, 2022)
Background: “Mestringskatten” and “Mestringskatten for ungdom” are treatment programs for children and adolescents with separation anxiety disorder, social anxiety disorder, and/or generalized anxiety disorder. Mestringskatten (7–13 years) and Mestringskatten for ungdom (14–17 years) are structured, manualized cognitive behavioural therapy (CBT) programs emphasising cognitive restructuring techniques and gradual exposure training. The programs are delivered both as individual and as group treatments. The main aim of the programs is to reduce anxiety symptoms and/or recovery from anxiety disorder. The programs are translations and adaptations of the original Coping Cat program (child version) and the C.A.T. project (adolescent version). The Norwegian child version comprises 12 sessions whereas the adolescent version comprises 14 sessions. Two additional parents only sessions are included in both versions. Therapist manuals and workbooks for children and adolescents have been published by Universitetsforlaget (www.universitetsforlaget.no) who is the owner of the programs in Norway. The present article is a revision of two previous Ungsinn reviews on Mestringskatten (Bratt, 2010; Haugland & Bjåstad, 2017). Method: The review is based on two literature searches, one in 2016 and the other in 2020. The following databases were included in these searches: Mbase, Medline, Psykinfo, NORART, Cochrane, Cristin, NORA, SCOPUS, SweMed, Kunnskapssenteret, NREPP, NICE, Blueprints, and CEBC. Information was also obtained from RBUP Øst og Sør who is responsible for the Norwegian translation and training in the programs. Results: Mestringskatten and Mestringskatten for ungdom have good theoretical basis within CBT. The interventions are very well described in manuals and workbooks. The effect of the original child version, Coping Cat, has been documented through many international efficacy studies, as well as in previous reviews and meta-analyses. Some documentation of effect for is found in international studies for the C.A.T. project. A Norwegian randomized control effectiveness study has been published, with results indicating that Mestringskatten was effective compared to a wait-list control group. The study included children (7-13 years) recruited from ordinary child and adolescent mental health clinics. Mestringskatten was effective when delivered as group as well as individual treatment. However, children with social anxiety had better outcomes from group treatment. Treatment outcomes were maintained at 2-year follow-up. No studies were identified for Mestringskatten for ungdom. A two-day voluntary training workshop is available, and supervision can be arranged. However, there are no systems to ensure implementation quality of the program, indicating uncertainty as to how the programs are used in clinical practice in Norway. Conclusion: Mestringskatten and Mestringskatten for ungdom are well described programs with good theoretical foundation. One Norwegian effectiveness study with good research quality confirms the effect of Mestringskatten for children. No research study has been found on the effect of Mestringskatten for ungdom. Lack of systems to ensure implementation quality leads to uncertainty as to how the programs are used in clinical practice in Norway. Based on Ungsinn’s criteria, Mestringskatten (7-13 years) applied in usual practice in Norway is classified at level 4: Intervention with satisfactory evidence of effectiveness. Mestringskatten for ungdom (14-17 years) is classified at level 3: Intervention with some documentation of effect.